Simulation modeling of the group of multimodal cargo lines including water transport - Kazakov, Nikolay (Transport, 2006)
The aim of this paper is to present the concept of making a simulation model of the multimodal cargo lines group including water transport and the principles of its formation in the form of interconnected similar modules. The paper presents a generalized algorithm for choosing the optimum multimodal transportation variant on the basis of simulation modeling. The matter of the paper is given on the example of the organization of export and import cargoes multimodal transportation by Belarus in southern direction.First Published Online: 27 Oct 2010